Diagnostic accuracy and cytomorphology analysis of fine-needle aspiration of salivary glands (Medical Journal of Indonesia, 2012)
Background: Fine-needle aspiration (FNA) is an effective and safe procedure for analyzing salivary gland lesions. Various morphological and overlapping cytomorphology features can bring difficulty in diagnosis of the salivary gland lesions. This study aimed to evaluate the diagnostic accuracy of fine needle aspiration cytology of salivary glands lesions. Methods: There were 107 cases of cytology and 39 cases of histopathology of salivary gland lesions collected and reviewed from the archives of Anatomical Pathology Department, Faculty of Medicine, Universitas Indonesia / Cipto Mangunkusumo Hospital from 2005-2009. Seven cases of cytology were excluded, due to unsatisfactory specimens. Diagnostic test was applied to analyze the 39 pairs of cytology-histopathology cases. Results: There were 100 cases of salivary gland lesions cytology obtained, consisted of 27 negatives, eight cases inconclusive and 65 cases of neoplastic lesions. Of the 39 pair cases, fourteen cases showed result discrepancies between cytology and histopathology, with 3 false-negative cases and 1 false-positive case. The sensitivity and specificity of cytology analysis in differentiating malignant from non-malignant lesions were 82.35%, and 95.45% respectively, NPV 87.5% and PPV 93.34%. Conclusion: This study showed diagnostic accuracy of FNA cytology salivary gland lesions was varied, with 82.35% sensitivity and 95.45% specificity in differentiating malignant from non-malignant hence this information can still be used for case management. (Med J Indones. 2012;21:92-6)